PERLINDUNGAN HUKUM KEPADA SAKSI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DALAM SISTEM PERADILAN PIDANA INDONESIA - Rizqi Alfajri (2023)
The problem of sexual violence is a phenomenon of the tip of the iceberg in Indonesia. The large number of cases of violence in the form of sexual violence such as rape, pornography, and domestic sexual violence that have not been handled has created complexity in the handling of victims of sexual violence. With the promulgation of Law number 12 of 2022 concerning Crimes of Sexual Violence in 2022, it is hoped that it will be a turning point in efforts to guarantee the rights of a victim-witness to be able to testify safely in the criminal justice system in Indonesia. However, in practice there are still many cases of sexual violence that have not been handled, which means that the handling, protection and recovery of victims or victims who testify in their own trials or are called witness-victims have not been carried out optimally. The author in this study is interested in examining the rights obtained from a witness who is a victim of sexual violence in the Indonesian criminal justice system and its protection and recovery using normative juridical research methods along with statutory and conceptual approaches. The authors in this research found that there are still many problems in providing legal protection to witnesses who are victims of sexual violence which has resulted in cases of sexual violence becoming a phenomenon of the tip of the iceberg in Indonesia where there are many cases or incidents of sexual violence that are not reported or even reports of sexual violence that are not processed at this stage. which is further.